Westcott's Plant Disease Handbook - Horst, R. Kenneth; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
In its revised, improved and expanded 7th Edition, Westcott's Plant Disease Handbook presents newly discovered diseases and newly identified hosts in the classic format that has won favor with readers at every level of expertise and experience. Dictionary-style entries permit easy access to essential information, and numerous illustrations help identify important diseases. New and updated material includes significant taxonomic changes in fungi, bacteria, viruses and nematodes; recently discovered diseases and new hosts for previously known plant-pathogens; changes in chemicals and pesticides and updates on regulations governing their use; integrated pest management and biological control. The Handbook offers additional conveniences: useful cross references, indexes, illustrative plates of 34 key diseases, and 40 black and white illustrations of other diseases. This updated edition of a long-trusted resource will serve a broad audience, from amateur backyard gardeners to landscape architects, arborists, florists, nursery professionals and plant scientists.
Introduction -- Garden Chemicals and Their Application -- Classification of Plant Pathogens -- Plant Diseases and Their Pathogens -- Host Plants and Their Diseases -- List of Land Grant Institutions and Diagnostic Laboratories -- Glossary -- Selected Bibliography -- Index.
Keywords: LIFE SCIENCES; AGRICULTURE; BOTANY; PLANT DISEASES; PLANT PHYSIOLOGY; LIFE SCIENCES; PLANT PATHOLOGY; PLANT SCIENCES; PLANT PHYSIOLOGY; AGRICULTURE; LIFE SCIENCES, GENERAL